Quality of care and 30 day mortality among patients with hip fractures: a nationwide cohort study - Ingeman Annette; Johnsen Søren P; Pedersen Lars; Thomsen Marianne; Jensen Claus M; Jensen Niels C; Nielsen Katrine A; Bartels Paul D; Thomsen Reimar W (BMC, 2009)
Abstract Background We examined the association between quality of care and 30 day mortality in a nationwide cohort of patients hospitalized with hip fracture. Methods We used data from The Danish National Indicator Project, a quality improvement initiative with participation of more than 90% of Danish hospital departments caring for patients with hip fracture between August 16, 2005 and August 15, 2006. Quality of care was measured in terms of meeting five specific criteria: early assessment of the patient's nutritional risk, systematic pain assessment during mobilization, assessment of Activities of Daily Living (ADL) before the fracture, assessment of ADL before discharge, and initiation of treatment to prevent future osteoporotic fractures. The association between meeting each of the quality of care criteria for the patient and 30 day mortality was examined using logistic regression to adjust for potential confounders. Results 6,266 patients hospitalized with an incident episode of hip fracture were included in the study. For four of the five quality of care criteria, patients who met the criterion had substantially lower 30 day mortality after hip fracture. The adjusted mortality odds ratios (ORs) ranged from 0.42 (95% CI, 0.30 to 0.58) for assessment of ADL before discharge (excluding deaths during hospitalization) to 0.72 (95% CI, 0.52 to 1.00) for systematic pain assessment. We found an inverse dose-response relationship between the number of quality of care criteria met and 30 day mortality; the lowest mortality was found among patients for whom all five quality of care criteria were met, as compared with patients for whom no quality of care criteria were met: adjusted mortality OR 0.18 (95% CI, 0.09 to 0.36). Conclusion Higher quality of care during hospitalization with hip fracture was associated with lowered 30 day mortality.